The Concept Of Corruption According To The Perspective Of Islamic Criminal Law - Syarbaini, Ahmad; Lubis, Andi Hakim; Bin Abdulsomad, Muhammat Faosan Dohae (Journal of Mujaddid Nusantara, 2024)
Corruption comes from the Latin coruptio and corruptus which means to bribe and corrumpere which means to destroy. Corruption is included in jarîmah. Jarîmah is: "Prohibitions of syara', namely; Threats with 'uqūbat had or ta'zir". Ta'zir is: "'uqūbat determined by the authorities in order to refuse thinning and prevent crime". Corruption in Indonesian law is: "Unlawfully committing acts of enriching oneself or another person or a corporation that can harm state finances or the state economy". While the terms that are close to corruption in Islamic studies are: "ghulūl, ikhtilâs, risywah and al-fasad and". Corruption according to fiqh is: "It is a jarîmah or a modern and extraordinary crime for which there is no agreement on the terms and definitions. While the 'uqūbat is ta'zîr which is returned to waliyul amri".